SARcopenia Assessment in Hypertension: The SARAH Study - Kara, Murat; Kara, Özgür; Ceran, Yasin; Kaymak, Bayram; Kaya, Tuğçe Cansu; Çıtır, Beyza Nur; Durmuş, Mahmut Esad; Durmuşoğlu, Esra; Razaq, Sarah; Doğan, Yahya; Shehab, Dia; Alkandari, Salem A; et al. (American journal of physical medicine & rehabilitation, 2023)
OBJECTIVES: The aims of the study were to investigate the relationship between sarcopenia and renin-angiotensin system-related disorders and to explore the effects of angiotensin-converting enzyme inhibitors and angiotensin II receptor blockers on muscle mass/function and physical performance. DESIGN: This multicenter, cross-sectional study was performed using ISarcoPRM algorithm for the diagnosis of sarcopenia. RESULTS: Of the 2613 participants (mean age = 61.0 ± 9.5 yrs), 1775 (67.9%) were hypertensive. All sarcopenia-related parameters (except chair stand test in males) were worse in hypertensive group than in normotensive group (all P < 0.05). When clinical/potential confounders were adjusted, hypertension was found to be an independent predictor of sarcopenia in males (odds ratio = 2.403 [95% confidence interval = 1.514-3.813]) and females (odds ratio = 1.906 [95% confidence interval = 1.328-2.734], both P < 0.001). After adjusting for confounding factors, we found that all sarcopenia-related parameters (except grip strength and chair stand test in males) were independently/negatively related to hypertension (all P < 0.05). In females, angiotensin-converting enzyme inhibitors users had higher grip strength and chair stand test performance values but had lower anterior thigh muscle thickness and gait speed values, as compared with those using angiotensin II receptor blockers (all P < 0.05). CONCLUSIONS: Hypertension was associated with increased risk of sarcopenia at least 2 times. Among antihypertensives, while angiotensin-converting enzyme inhibitors had higher muscle function values, angiotensin II receptor blockers had higher muscle mass and physical performance values only in females.
Keywords: Muscle Strength; Hypertension; Aged; lidé středního věku; senioři; antagonisté receptorů pro angiotenzin; lidé; hypertenze; Middle Aged; svalová síla; inhibitory ACE; Female; síla ruky; průřezové studie; Angiotensin-Converting Enzyme Inhibitors; Male; ženské pohlaví; Cross-Sectional Studies; sarkopenie; Humans; mužské pohlaví; Sarcopenia; Hand Strength; Angiotensin Receptor Antagonists